ANALISIS KOMPETENSI GURU DALAM PROSES PEMBELAJARAN PADA MATA PELAJARAN EKONOMI DI SMA - Asmita, Etin; Witarsa, Witarsa; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is titled "Analysis of Teacher Competence in Learning Processes in Economic subjects in SMA Negeri 2 Sungai Raya". This research is motivated by the importance of the role of teacher competence in carrying out tasks and professions as teaching staff in the scope of school organizations. A teacher who has competence in his profession will be able to carry out his duties properly and efficiently, effectively, on time, and in accordance with the objectives.The purpose of this study is to describe the level of competence of teachers as teachers in schools. The sample in this study amounted to 30 people. This research uses descriptive qualitative research type. The type of data consists of primary data obtained through filling out questionnaires by student respondents, while secondary data are sourced from SMA Negeri 2 Sungai Raya data, documents, and regulations relating to the problem to be examined.Teacher Competency, Economics Teacher at SMA Negeri 2 Sungai Raya is measured by looking at 3 (three) dimensions of competency, namely personal competence, professional competence, and social competence. From the calculation of all indicators, the results of the study indicate that the level of competence of teachers has an average each different. Teachers' personal competencies and social competencies have the highest average compared to professional competencies that have the lowest average. This proves the level of professional competence still needs to be increased to match what is expected.Â Keywords: Teacher Competency